Enhanced concrete performance in cracking resistance and chloride penetration using hybrid fiber blends. (2022) - Bhogone, Manjunath V.; Subramaniam, Kolluru V.L.
Abstract: The fracture response and resistance to chloride penetration of concrete reinforced with discrete steel fibers (SF) and hybrid blend of steel and macro polypropylene fibers (HyFRC) are evaluated. A significant improvement in fracture response is obtained in HyFRC compared to SF. Cohesive stress-crack opening ( σ-w ) relationships are obtained for the concrete with and without discrete reinforcement from the measured fracture test responses. The hybrid fiber blend has a higher tensile strength and a significantly higher stress resistance to crack opening when compared to an identical volume fraction of steel fibers. HyFRC also exhibit a lower chloride penetration when compared to control and SF concrete mixtures. The hybrid blend of steel and polypropylene fibers provides improved structural performance due to enhanced resistance to crack opening and an improvement in the durability by reducing the chloride penetration in concrete.